2006
DOI: 10.1111/j.1939-1676.2006.tb02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine Mast Cell Tumors: Correlation of Apoptosis and Proliferation Markers with Prognosis

Abstract: The Patnaik histologic grading system is commonly used to predict the behavior of cutaneous mast cell tumors (MCTs) in dogs, but it is less useful for grade 2 MCTs because they exhibit considerable variation in biological behavior. In this retrospective study, immunohistochemical staining for Ki-67, proliferating cell nuclear antigen (PCNA), and survivin and a standardized argyrophilic staining of nucleolar organizer regions (AgNOR) protocol were performed on 121 archived paraffin-embedded specimens of canine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
3
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 35 publications
4
132
3
15
Order By: Relevance
“…17,31 Metastasis in cMCT has been associated with a poor prognosis 17 and this behavior has been mainly related to grade. 13,32,33 Grade I MCT has an excellent prognosis, grade III has a poor prognosis and often metastasizes. On the other hand, the clinical behavior and survival rate in dogs with grade II cMCT is uncertain with metastatic rate between 5 and 22%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,31 Metastasis in cMCT has been associated with a poor prognosis 17 and this behavior has been mainly related to grade. 13,32,33 Grade I MCT has an excellent prognosis, grade III has a poor prognosis and often metastasizes. On the other hand, the clinical behavior and survival rate in dogs with grade II cMCT is uncertain with metastatic rate between 5 and 22%.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the clinical behavior and survival rate in dogs with grade II cMCT is uncertain with metastatic rate between 5 and 22%. 2,5,9,[33][34][35] The prevalence of positive evidence of mast cell infiltration at distant sites found in this retrospective study could have been overestimated because the sample population investigated was selected based on specific inclusion criteria (eg, minimum follow-up, cytology of spleen and liver).…”
Section: Discussionmentioning
confidence: 99%
“…Three dogs had subcutaneous mast cell tumours that underwent Kiupel grading only (Kiupel et al 2011 ), while four dogs had both Kiupel and Patnaik grading performed on their tumour. The Ki-67 (Scase et al 2006 ), Kiupel grading results and mitotic index (Romansik et al 2007 ) are shown in Table 1 . None of the tumours had undergone immunohistochemistry staining for KIT or PCR analysis for c-KIT mutations.…”
Section: Population Data and Tumour Characteristicsmentioning
confidence: 99%
“…For example, Ki67 is a large nuclear protein that is expressed exclusively by cells in all phases of the cell cycle except G0, and so if a cell is expressing Ki67, it is replicating. It is an independent prognostic factor in many human tumours, and it has been shown to be an independent prognostic factor in canine MCTs (Scase et al 2006).…”
Section: Pathology and Clinical Pathologymentioning
confidence: 99%
“…Ki67 protein expression is used as an indirect marker of cellular proliferation. Scase et al (2006) reported using a cut-off of 1.8% Ki67+ cells predicted survival, independently of tumour grade. One-, 2-and 3-year survival rates were 92, 86 and 77% for low Ki67 and 43, 21 and 21% for high Ki67.…”
Section: Example 2: Canine Mctsmentioning
confidence: 99%